Dynamic load balancing policy with communication and computation elements in grid computing with multi-agent system integration - Yahaya, Bakri; Latip, Rohaya; Othman, Mohamed; Abdullah, Azizol (The Society of Digital Information and Wireless Communications, 2011)
The policy in dynamic load balancing, classification and function are variety based on the focus study for each research. They are different but employing the same strategy to obtain the load balancing. The communication processes between policies are explored within the dynamic load balancing and decentralized approaches. At the same time the computation processes also take into consideration for further steps. Multi-agent system characteristics and capabilities are explored too. The unique capabilities offered by multi-agent systems can be integrated or combined with the structure of dynamic load balancing to produce a better strategy and better load balancing algorithm.